The moderating role of interpersonal problems on baseline emotional intensity and emotional reactivity in individuals with borderline personality disorder and healthy controls. Issue 4 (26th November 2022) - Di Bartolomeo, Alyssa A.; Varma, Sonya; Fulham, Lindsay; Fitzpatrick, Skye
Emotion dysregulation, including higher baseline emotional intensity and emotional reactivity (i.e., increased magnitude of change in emotional responding) is theoretically central to Borderline Personality Disorder (BPD). However, little research has examined which specific emotions individuals with BPD experience emotion dysregulation in. Interpersonal problems also theoretically drive emotion dysregulation in BPD. However, whether interpersonal problems elicit emotion dysregulation for some specific emotions but not others is unclear. This study aimed to assess whether interpersonal problems moderate the relationship between (1) baseline emotional intensity and (2) emotional reactivity in BPD across six specific emotions (i.e., sadness, disgust, fear, shame, guilt, and anger). Borderline Personality Disorder ( n = 30) and healthy control (HC; n = 30) groups reported their interpersonal problems at baseline and their emotions before and after listening to a laboratory stressor. For the BPD (but not HC) group, higher interpersonal problems were associated with greater baseline sadness, disgust, fear, shame, and guilt. Across groups, higher interpersonal problems were associated with greater sadness, fear, guilt, and anger, but not disgust, reactivity. Higher interpersonal problems were associated with higher shame reactivity specifically for those with BPD. Targeting interpersonal problems may reduce heightened baseline emotional intensity and emotional reactivity for those with BPD, particularly for shame reactivity in BPD.